2016
DOI: 10.1136/medethics-2016-103612
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic appropriation: a new concept in the ethics of clinical research

Abstract: Ethical concerns about therapeutic misconception have been raised since the early 1980s. This concept was originally described as research participants' assumptions that decisions relating to research interventions are made on the basis of their individual therapeutic needs. The term has since been used to refer to a range of 'misunderstandings' that research participants may have. In this paper, we describe a new concept-therapeutic appropriation Therapeutic appropriation occurs when patients, or clinicians, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Rather, the men demonstrated awareness of the research aims and simultaneously hoped to benefit from an incidental aspect of the study: surveillance for prostate cancer risk. The opportunistic approach to enhancing one's clinical care, through research participation, has been labeled “therapeutic appropriation” (McDougall et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the men demonstrated awareness of the research aims and simultaneously hoped to benefit from an incidental aspect of the study: surveillance for prostate cancer risk. The opportunistic approach to enhancing one's clinical care, through research participation, has been labeled “therapeutic appropriation” (McDougall et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Joffe and Weeks 19 have shown that not only patients but also physicians and investigators might share such misconceptions of clinical trials. 20 This is further discussed by McDougall et al., 21 who suggest a new concept, therapeutic appropriation (TA). TA occurs, they state, when ‘patients, or clinicians, actively reframe research participation as an opportunity to enhance patients’ clinical care, while simultaneously acknowledging the generalised research aims’.…”
Section: Discussion: the Culture Of Hopementioning
confidence: 96%
“…This paper reports on the findings from the physicians only, with the findings from the patient interviews reported elsewhere. 19 The primary care clinics were selected using purposive sampling, to capture general and specialist (for example, women's health) primary care practices who were involved in clinical research. Contact with the clinics was established through primary care research networks and public listings.…”
Section: Methodsmentioning
confidence: 99%